2020
DOI: 10.21203/rs.3.rs-34829/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and attitude regarding risk factors of cardio vascular disease among general people residing in Nepalgunj, Banke; Nepal

Abstract: Abstract Background Cardio vascular disease (CVD), a group of disorders of heart and blood vessels. It is the leading cause of death globally including Nepal. The major factors which increase the risks are tobacco chewing/smoking, raised blood cholesterol level, high blood pressure, physical inactivity, overweight, obesity, excessive alcohol consumption, age, sex and heredity etc. Therefore, the aim of this study was to assess the level of knowledge and attitude regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Similarly, in our study 45.8% of respondent answered 1 hour exercise is needed to prevent the CVDs, which is contrast to the finding of study done in Nepalgunj where most of the respondents 80.7% answered 1 hour. 16 In this study 24.2% of the respondent had the adequate level of knowledge. This finding is supported by the study conducted at Sahid Gangalal Hospital which showed that 28% of respondent had adequate level of knowledge.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly, in our study 45.8% of respondent answered 1 hour exercise is needed to prevent the CVDs, which is contrast to the finding of study done in Nepalgunj where most of the respondents 80.7% answered 1 hour. 16 In this study 24.2% of the respondent had the adequate level of knowledge. This finding is supported by the study conducted at Sahid Gangalal Hospital which showed that 28% of respondent had adequate level of knowledge.…”
Section: Resultsmentioning
confidence: 61%
“…2 Similarly this finding is similar to another study done in Sahid Gangalal Hospital where there is significant association of knowledge with gender, education. 16 This might be due to similar socio demographics characteristics of participants in both studies and the study setting and also somehow similarities of the tools used. The study finding concluded that 41.3% of respondents have inadequate level of knowledge regarding the myocardial infarction despite the high literacy level 92.1% among which less than half 17.6% had higher than secondary level education.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the knowledge, attitude, and practices of diabetes done in Nepal and elsewhere target patients with diabetes. (2,14,16,19) Unlike these, this study targeted the diabetic patients. A formal assessment of diabetes knowledge of subjects with diabetes can be carried out by administering the DKQ in daily clinical practice with this simple DKQ either with written or oral evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…(13) Poor diabetes knowledge has a negative impact on selfcare behavior. (14)(15)(16)Though health education of diabetic patients has an effective role in the proper management of diabetes, there is a shortage of well trained personnel in Nepal to provide appropriate education about diabetes mellitus and its associated co-morbidities and complications. (1,17) A formal assessment of knowledge about diabetes mellitus and its management of a diabetic patients is a prerequisite.…”
Section: Main Text Introductionmentioning
confidence: 99%